Muscle Activation Signals During Gait Parkinson’s Disease are More Rhythmic than in Healthy Controls - Timothy Adam Thrasher; Stanley Fisher (Journal of Neurological Research And Therapy, 2016)
Background To quantify the underlying rhythmic patterns observed in surface electromyography (SEMG) in patients with Parkinson’s Disease (PD), to compare rhythmicity of PD gait with normal gait, and to compare overground walking to treadmill gait. Methods Eight individuals with idiopathic PD, and ten individuals with no history of neurological disorders participated. SEMG was recorded from the vastus lateralis, tibialis anterior, lateral gastrocnemius and biceps femoris muscles bilaterally. Each participant performed two trials of overground walking and two trials of treadmill walking at a self-selected comfortable walking speed. SEMG was analyzed using a non-linear statistical model that identified underlying recurrent locomotor patterns, which estimated the relative contribution of central pattern generators to the observed muscle activation signals. An index of rhythmicity was determined from the statistic, R2. Results The rhythmicity of PD gait was significantly higher than that of normal gait (p = .0458). There was also a significant difference between the rhythmicity of overground walking and treadmill walking (p = .0097). Conclusions Individuals with PD appear to walk with muscle activation patterns that are more rhythmic than normal. This suggests that there is more stride-to-stride consistency, and there are fewer postural adjustments and responses to perturbations. We also found that treadmill gait was more rhythmic than overground walking. These findings, although preliminary, challenge the paradigm and current approach to gait retraining of patients with PD.
Keywords: Surface electromyography (SEMG)